Jamaica : Eighth Review Under the Arrangement Under the Extended fund Facility and Request for Waiver for the Nonobservance of Performance Criterion and Modification of Performance Criteria. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Jamaica's Eighth Review Under the Arrangement Under the Extended Fund Facility (ECF) and Request for Waiver for the Nonobservance of Performance Criterion (PCs) and Modification of PCs. Jamaica's economic performance under the authorities' economic program is on track and has remained strong. All PCs for end-March 2015 were met, with the exception of the central government primary balance criterion, which was narrowly missed. Structural reforms have advanced broadly in line with the program. The IMF staff supports the authorities' request for completion of the eighth review of the arrangement under the ECF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet